Opioid Use Patterns in a Statewide Adult Medicaid Population Undergoing Elective Lumbar Spine Surgery. Issue 3 (1st February 2023) - Reitman, Charles A.; Ward, Ralph; Taber, David J.; Moran, William P.; McCauley, Jenna; Basco, William T.; Gebregziabher, Mulugeta; Lockett, Mark; Ball, Sarah J.
Abstract : Study Design: Retrospective administrative database review. Objective: Analyze patterns of opioid use in patients undergoing lumbar surgery and determine associated risk factors in a Medicaid population. Summary of Background Data: Opioid use in patients undergoing surgery for degenerative lumbar spine conditions is prevalent and impacts outcomes. There is limited information defining the scope of this problem in Medicaid patients. Materials and Methods: Longitudinal cohort study of adult South Carolina (SC) Medicaid patients undergoing lumbar surgery from 2014 to 2017. All patients had continuous SC Medicaid coverage for 15 consecutive months, including six months before and nine months following surgery. The primary outcome was a longitudinal assessment of postoperative opioid use to determine trajectories and group-based membership using latent modeling. Univariate and multivariable modeling was conducted to assess risk factors for group-based trajectory modeling and chronic opioid use (COU). Results: A total of 1455 surgeries met inclusion criteria. Group-based trajectory model demonstrated patients fit into five groups; very low use (23.4%), rapid wean following surgery (18.8%), increasing use following surgery (12.9%), slow wean following surgery (12.6%) and sustained high use (32.2%). Variables predicting membership in high opioid use included preoperative opioid use, younger age, longer length of stay, concomitant medications, and readmissions. More than three quarter of patients were deemed COUs (76.4%). On bivariate analysis, patients with degenerative disk disease were more likely to be COUs (24.8% vs. 18.6%; P =0.0168), more likely to take opioids before surgery (88.5% vs. 61.9%; P <0.001) and received higher amounts of opioids during the 30 days following surgery (mean morphine milligram equivalents 59.6 vs. 25.1; P <0.001). Conclusions: Most SC Medicaid patients undergoing lumbar elective lumbar spine surgery were using opioids preoperatively and continued long-term use postoperatively at a higher rate than previously reported databases. Preoperative and perioperative intake, degenerative disk disease, multiple prescribers, depression, and concomitant medications were significant risk factors.